Assessing the perfectionistic disposition of collegiate student-athletes and its impacts in team effort in cheerleading - Bringel, Monn Robin L. 2000-
Perfectionism, characterized by the pursuit of excessively high standards and a relentless quest for flawlessness, is a multifaceted personality trait that can act as a double-edged sword. It has the potential to both enhance and hinder an athlete's performance and team effort. This study aims to explore how perfectionism influences collegiate cheerleading athletes, with a focus on understanding its causes and effects on their efforts to help their team, both positively and negatively. This study aims to identify the predisposing factors and levels of Perfectionism among Cheerleading Collegiate Student-athletes and its impact on team effort. Frost Multidimensional Perfectionism Scale (FMPS) and a self-administered written interview were distributed to the Varsity Pep Squad in a university in Metro Manila (N = 19). The results of FMPS were scored by percentages. Descriptive statistics was applied to assess the answers from the written interview. FMPS showed Personal Standard was a leading variable with 84.83%. This refers to an athlete’s set of rules or expectations they have set for themselves to achieve or abide to. Collectively, the participants had a perfectionism score of 71.46%. The findings of the study indicate that self-oriented and team-oriented perfectionism may influence a team’s performance positively. Personal Standard as a predominant variable among the predisposing factors of Perfectionism among Cheerleading Collegiate Athletes shows to have a positive effect on Team Effort